# I need help with the following problem:

Solve the equation:

(x/2x+2)= (-2x/4x+4) + (2x-3/x+1)

## I am not sure whether I am interpreting your question correctly.

.5x + 2 = -.5x + 4 + 2x - 3/x + 1

First, get all the x terms on one side.

.5x + .5x - 2x + 3/x = 4 + 1 - 2

Combine terms.

-x + 3/x = 3

Multiply both sides by x to get rid of x in the denominator.

-x^2 + 3 = 3x

Transpose.

-x^2 - 3x + 3 = 0

Multiply by -1.

x^2 + 3x - 3 = 0

Unfortunately, I cannot factor this to find possible answers. Are there any typos in your equation?

I hope this helps a little. Thanks for asking.

## n(5^2x1/25)=3

## lol sorry i was suppose to give you the answer..i have never done this before...

## To solve the equation, we need to find the value of x that satisfies the given equation. Let's simplify the equation step by step.

First, let's simplify each fraction on the right side of the equation:

(x/2x+2) = (-2x/4x+4) + (2x-3/x+1)

To simplify the fractions, we need to find their common denominators.

The common denominator for 2x+2 and 4x+4 is 2(x+1). Multiplying the numerator and denominator of the first fraction by (x+1), we get:

[(x/2x+2) * (x+1)] = (-2x/4x+4) + (2x-3/x+1) * (2x+1)

Simplifying further, we have:

(x(x+1)/(2(x+1))) = (-2x/4(x+1)) + ((2x-3)(2x+1)/(x+1))

Now, let's simplify the equation further by clearing the denominators:

x(x+1) = -2x + (2x-3)(2x+1)

Expanding the parentheses and combining like terms, we have:

x^2 + x = -2x + 4x^2 - x - 3

Rearranging this equation, we have:

x^2 + x = 4x^2 - 2x - 3

Next, let's move all terms to one side of the equation:

x^2 - 3x^2 + x + 2x - 3 = 0

Combining like terms, we get:

-x^2 + 3x - 3 = 0

To solve this quadratic equation, we can either factor it or use the quadratic formula. Let's use the quadratic formula: x = (-b ± √(b^2 - 4ac)) / (2a)

In this case, a = -1, b = 3, and c = -3.

Substituting the values into the quadratic formula, we have:

x = (-(3) ± √((3)^2 - 4(-1)(-3))) / (2(-1))

Simplifying further, we have:

x = (-3 ± √(9 - 12)) / (-2)

x = (-3 ± √(-3)) / (-2)

Since we have a square root of a negative number, the equation has no real solutions. Hence, there are no values of x that satisfy the given equation.